Social media influencer’s content credibility on information adoption and purchase intention of beauty product among generation Z in Malaysia - Siti Nor Bayaah Ahmad; Ikmal Malik; Stephen Laison Sondoh Jr.; Nor Asiah Mahmod (Atlantis Press, 2024)
The present study seeks to investigate the impact of influencer credibility characteristics (attractiveness, trustworthiness, expertise, and homophily) on beauty product purchase decisions using information adoption as a moderator. The information was gathered online from 136 university students in the Klang Valley and east Malaysia. The data of this study were analysed using partial least squares structural modelling (PLS-SEM). Except for attractiveness, the results showed that expertise, homophily, and trustworthiness have a significant indirect positive effect on information adoption and purchase decision. The findings contributed to a better understanding of the credibility of influencers, which can have practical implications for marketers developing effective marketing strategies via digital platforms. Furthermore, the study's findings revealed that consumers prefer influencers who are highly trusted due to their significant competence in the industry in which they work rather than relying solely on their physical appeal. According to the findings of this study, beauty brands targeting Generation Z should consider collaborating with credible social media influencers to increase their credibility and purchase intention among the target audience. This study is able to add value to the current understanding of the primary antecedents of younger consumer engagement by examining these dimensions of perceived credibility as well as information adoption behaviour.